2016
DOI: 10.2459/jcm.0000000000000311
|View full text |Cite
|
Sign up to set email alerts
|

Long-term events following atrial fibrillation rate control or transcatheter ablation

Abstract: Considering this multicenter design study, AVK continuation following AFTCA, especially within patients with low-to-intermediate thromboembolic risk, confers a hemorrhagic risk greater to the thromboembolic protective effect. All thromboembolic events following AFTCA occur within patients experiencing atrial fibrillation relapses; therefore, in patients with high thromboembolic risk routine rhythm monitoring is essential after AVK discontinuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 23 publications
0
31
0
1
Order By: Relevance
“…After screening for the full-text articles, we excluded those that did not have specific number or percentage in observation group, control group, or outcome numbers. Finally, seven studies [28][29][30][31][32][33][34] have met the criteria and were included in the meta-analysis. The main characteristics of the eligible studies are shown in Table 1.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening for the full-text articles, we excluded those that did not have specific number or percentage in observation group, control group, or outcome numbers. Finally, seven studies [28][29][30][31][32][33][34] have met the criteria and were included in the meta-analysis. The main characteristics of the eligible studies are shown in Table 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…who had undergone RFCA for AF and who were free from AF as documented by conventional 24-hour Holter monitoring 29,31,33,34,39. Recently, there have been some studies that advocate safe discontinuation of OACs after weighing the risk of bleeding in patients with CHADS 2 < 2 and restoring sinus rhythm after RFCA [39][40][41][42][43].…”
mentioning
confidence: 99%
“…Hence, it is suggested to continue long-term oral anticoagulation therapy in all patients at high thromboembolic risk, i.e. CHA 2 DS 2 -VASc ≥2, regardless of the AF ablation outcome29. However, it has been shown recently that all thromboembolic events following AF ablation occur in patients who experienced arrhythmia recurrence (4% among patients with AF recurrence vs. 0% among those who were arrhythmia-free post procedure, p < 0.001)29.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown recently that all thromboembolic events following AF ablation occur in patients who experienced arrhythmia recurrence (4% among patients with AF recurrence vs. 0% among those who were arrhythmia-free post procedure, p < 0.001)29. These findings emphasize the importance of an early detection of AF recurrence after ablation1345678910111217182829. Therefore, identification of patients at high risk for the delayed AF re-occurrence could determine the strategy for long-term rhythm monitoring of patients for whom it was believed to have been “cured” based on the freedom from arrhythmia at 1 year post ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Trwają kolejne próby kliniczne służące porównaniu nieprzerwanego leczenia za pomocą VKA i NOAC u pacjentów z AF poddawanych ablacji, np. wskazują na stosunkowo małą częstość występowania udarów mózgu w pierwszych kilku latach po ablacji przezcewnikowej AF [737,[771][772][773][774][775][776], to trzeba brać pod uwagę długotermino-we ryzyko nawrotu AF oraz profil bezpieczeństwa leczenia przeciwzakrzepowego u pacjentów po ablacji. Ze względu na brak danych z kontrolowanych prób klinicznych OAC po ablacji przezcewnikowej powinno być prowadzone zgodnie z ogólnymi zaleceniami niezależnie od domniemanych wyników leczenia pod względem utrzymywania rytmu zatokowego.…”
Section: Leczenie Przeciwzakrzepowe Przed Ablacją Podczas Ablacji I unclassified